Sunlight irradiance and habituation of visual evoked potentials in migraine: The environment makes its mark. (June 2018) - Lisicki, Marco; D'Ostilio, Kevin; Erpicum, Michel; Schoenen, Jean; Magis, Delphine
Background: Migraine is a complex multifactorial disease that arises from the interaction between a genetic predisposition and an enabling environment. Habituation is considered as a fundamental adaptive behaviour of the nervous system that is often impaired in migraine populations. Given that migraineurs are hypersensitive to light, and that light deprivation is able to induce functional changes in the visual cortex recognizable through visual evoked potentials habituation testing, we hypothesized that regional sunlight irradiance levels could influence the results of visual evoked potentials habituation studies performed in different locations worldwide. Methods: We searched the literature for visual evoked potentials habituation studies comparing healthy volunteers and episodic migraine patients and correlated their results with levels of local solar radiation. Results: After reviewing the literature, 26 studies involving 1291 participants matched our inclusion criteria. Deficient visual evoked potentials habituation in episodic migraine patients was reported in 19 studies. Mean yearly sunlight irradiance was significantly higher in locations of studies reporting deficient habituation. Correlation analyses suggested that visual evoked potentials habituation decreases with increasing sunlight irradiance in migraine without aura patients. Conclusion: Results from this hypothesis generating analysis suggest that variations in sunlight irradiance may induce adaptive modifications in visual processing systems that could be reflected in visual evoked potentials habituation, and thus partially account for the difference in results between studies performed in geographically distant centers. Other causal factors such as genetic differences could also play a role, and therefore well-designed prospective trials are warranted.